Gut Microbiome–Targeted Regulation of Metabolic Syndrome Using Phyllostachys nigra–Derived Polysaccharides: Integrative Metagenomic and Metabolomic Analysis - Jesper Fowler; Peadeap Vorma; Haoyong Ding; Arun Basu (International Journal of Clinical and Translational Medicine, 2026)
Metabolic syndrome constitutes a global health crisis with complex etiological roots that extend beyond host genetics into the assembly and function of the gut microbiome. Emerging evidence indicates that polysaccharides derived from bamboo species such as Phyllostachys nigra can modulate the gut ecosystem toward improved glycolipid metabolism, yet translating these findings into safe, equitable, and scalable interventions demands integrative systems thinking that bridges multi-omics profiling, artificial intelligence, infrastructure design, and socio-technical governance. This paper presents a large-scale systems architecture for the targeted regulation of metabolic syndrome using Phyllostachys nigra-derived polysaccharides, driven by the synergistic integration of metagenomic and metabolomic analysis. We critically examine the end-to-end pipeline spanning data acquisition, cloud-native processing, AI-driven mechanism discovery, fairness-aware modeling, regulatory oversight, and sustainable deployment. The analysis foregrounds structural trade-offs between centralized and federated data architectures, model interpretability and predictive performance, and individual personalization versus population-level equity. Policy implications concerning data sovereignty, informed consent for microbiome data, supply chain resilience, and environmental sustainability of bamboo-based bioproducts are discussed in depth. Through a systems lens, the work illustrates how a single prebiotic candidate can be elevated from a bench finding to a robust, just, and governable socio-technical intervention.